Exposure to polystyrene nanoplastics impairs sperm metabolism and pre-implantation embryo development in mice - Yingdong Liu; Fengdan Hao; Haixin Liang; Wenqiang Liu; Yi Guo (Frontiers in Cell and Developmental Biology)
IntroductionMicroplastics and nanoplastics are prevalent environmental contaminants. Recent reports indicate that polystyrene nanoparticles may adversely impact male reproductive health. This study aims to examine the effects of polystyrene exposure on sperm metabolism and the development of pre-implantation embryos.MethodsIn this study, male C57BL/6 mice were orally gavage-administered polystyrene nanoplastics (60 nm, 20 mg/kg/day) for 35 days to assess their impact on male reproduction and early embryonic development. Experiments included testicular transcriptome analysis, sperm metabolomics, sperm motility and fertilization assays, embryonic ROS detection, and RNA sequencing of 2-cell embryos, revealing the adverse effects of polystyrene exposure on sperm metabolism and embryo development.ResultsThe results revealed that oral gavage of polystyrene to male mice induced a pronounced immune-inflammatory response in testicular tissue, reduced sperm motility, and significantly lowered the fertilization rate. Notably, sperm from treated mice exhibited substantial metabolic disruptions, affecting key pathways, including glycerophospholipid biosynthesis and DNA repair. After fertilization, embryos at the 2-cell stage suffered damage in apoptotic and DNA repair pathways, subsequently impairing early embryo development.DiscussionIn conclusion, this study demonstrated that the oral gavage administration of polystyrene nanoplastics to male mice significantly affects male reproductive function, resulting in abnormalities in early embryonic development and alterations in associated gene expression profiles. These findings offer essential scientific insights for future research into sperm-mediated transgenerational effects and their impact on early embryonic development.